G-Algebroids: a unified framework for exceptional and generalised geometry, and poisson-lie duality - Bugden,M; Hulik,O; Valach,F; Waldram,D (Fortschritte Der Physik/Progress of Physics, 2021)
We introduce the notion of urn:x-wiley:00158208:media:prop202100028:prop202100028-math-0001-algebroid, generalising both Lie and Courant algebroids, as well as the algebroids used in urn:x-wiley:00158208:media:prop202100028:prop202100028-math-0002 exceptional generalised geometry for urn:x-wiley:00158208:media:prop202100028:prop202100028-math-0003. Focusing on the exceptional case, we prove a classification of “exact” algebroids and translate the related classification of Leibniz parallelisable spaces into a tractable algebraic problem. After discussing the general notion of Poisson–Lie duality, we show that the Poisson–Lie U-duality is compatible with the equations of motion of supergravity.